Comparative genomics of Acinetobacter baumannii and therapeutic bacteriophages from a patient undergoing phage therapy - Mei Liu; Adriana Hernandez-Morales; James Clark; Tram Le; Biswajit Biswas; Kimberly A. Bishop-Lilly; Matthew Henry; Javier Quinones; Logan J. Voegtly; Regina Z. Cer; Theron Hamilton; Robert T. Schooley; et al. (Nature Communications, 2022)
A patient with a multidrug-resistant bacterial infection was successfully treated in 2016 using phage therapy. Here, the authors sequence the genomes of the therapeutic phages and three bacterial strains isolated before and during treatment, and show that the same mutations conferring phage resistance are found in in vitro-generated mutants and in phage-insensitive strains isolated from the patient.